2020
DOI: 10.3390/met10070881
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Phase Evolution upon Annealing of Fe76Si9−xB10P5Mox (x = 0, 1, 2 and 3) Alloys

Abstract: Alloying elements play an important role in adjusting the magnetic and thermal properties of Fe-based amorphous alloys. In this work, the effect of Mo addition on the thermal stability, structural evolution, and magnetic properties of Fe76Si9B10P5 metallic glass was studied. The study revealed that the substitution of a small amount of Mo (1 at.%) for Si enhances the glass-forming ability (GFA) but reduces the thermal stability of the alloy, causing a reduction of the supercooled liquid region. Substit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…This hypothesis is consistent with the larger transformation enthalpy determined in the Mo4 first crystallization peak. These results are also in agreement with the result by Perea [46] that found that the presence of Mo promotes the precipitation of Fe 23 B 6 -type phase, as in Nb case. On the other hand, Zr4-T1 alloy, as already commented, is the one with the most significant changes with the presence of two individual sextets at high field values and also the formation of regions or environments in the alloy with low values of the hyperfine magnetic field (below 10 T).…”
Section: Resultssupporting
confidence: 93%
“…This hypothesis is consistent with the larger transformation enthalpy determined in the Mo4 first crystallization peak. These results are also in agreement with the result by Perea [46] that found that the presence of Mo promotes the precipitation of Fe 23 B 6 -type phase, as in Nb case. On the other hand, Zr4-T1 alloy, as already commented, is the one with the most significant changes with the presence of two individual sextets at high field values and also the formation of regions or environments in the alloy with low values of the hyperfine magnetic field (below 10 T).…”
Section: Resultssupporting
confidence: 93%